2014
DOI: 10.1684/epd.2014.0679
|View full text |Cite
|
Sign up to set email alerts
|

Stereo‐electroencephalography (SEEG) in 65 children: an effective and safe diagnostic method for pre‐surgical diagnosis, independent of age

Abstract: Aim. We report our experience of stereoelectroencephalography (SEEG) in 65 children with drug‐resistant seizures, with a particular emphasis on young children. Methods. We retrospectively studied all SEEG performed between 2009 and 2011 in our centre. As SEEG can have several indications, the patients were classified into three categories, according to the probability of surgery. The contribution of SEEG to the final decision regarding surgery was evaluated for each category separately. We also compared the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 24 publications
6
72
1
Order By: Relevance
“…There were 12 studies that reported on epilepsy duration, with no significant difference between SEEG patients (mean = 126.8 months ± 65.0, median = 121.8) and SDE patients (mean = 62.4 months ± 51.1, median = 51.4; Table ). Among the SEEG patients, the etiology was identified as a temporal epileptogenic focus in 42.2% of patients, tumor in 6.7% of patients, FCD1 in 39.2% of patients, FCD2 in 10.7% of patients, and lesional in 41.5% of patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 12 studies that reported on epilepsy duration, with no significant difference between SEEG patients (mean = 126.8 months ± 65.0, median = 121.8) and SDE patients (mean = 62.4 months ± 51.1, median = 51.4; Table ). Among the SEEG patients, the etiology was identified as a temporal epileptogenic focus in 42.2% of patients, tumor in 6.7% of patients, FCD1 in 39.2% of patients, FCD2 in 10.7% of patients, and lesional in 41.5% of patients .…”
Section: Resultsmentioning
confidence: 99%
“…Among 490 SEEG-informed patients who underwent resective surgery from nine studies, 310 patients (61.0%, 95% CI = 60.5-61.4%) were seizure-free. 15,16,22,23,27,28,32,33,49 Of the 953 SDE-informed patients who underwent resective surgery from 21 studies, 564 patients (56.4%, 95% CI = 55.7-57.1%) were seizurefree. 18,20,21,24,25,[35][36][37][38][39][40][41][42][43][44][45]47,48,[50][51][52] Therefore, SEEG-informed surgical resections have associations that suggest better seizure freedom outcomes than SDE-informed surgical resections (WMD = +5.8%, 95% CI = 4.7-6.9%, P = .001).…”
Section: Epileptic Surgery and Outcomesmentioning
confidence: 99%
“…5,6,[8][9][10][11][12][13][14] Most centers either do not report or do not perform postexplant CTs routinely. Typically, complications due to electrode placement in SEEG are described as "major" or "symptomatic" without mention or discussion of any other types of bleeding seen on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although our total postimplant hemorrhage rate was 19.1%, the rate of symptomatic hemorrhage was 2.2%, similar to that reported in other SEEG studies as well as a recent systematic review. 5,6,[8][9][10][11][12][13][14] Most centers either do not report or do not perform postexplant CTs routinely. When including patients who had a symptomatic hemorrhage postexplant, our symptomatic hemorrhage rate was 3.5%.…”
Section: Discussionmentioning
confidence: 99%
“…In seven patients, an Engel class I outcome was achieved, along with neuropsychological and behavioural improvement. Taussig et al 27 used SEEG in 65 paediatric patients, 78% of whom underwent surgical resection. The mean clinical follow-up was 24 months, with 67% of children achieving an Engel class I outcome.…”
Section: Stereotactic Eegmentioning
confidence: 99%